Comprehensive Review of Inner Ear Anatomy on Photon-Counting CT - Rao, Dinesh; Murray, John V.; Agarwal, Amit K.; Sandhu, Sukhwinder Johnny; Rhyner, Pat A. (American Journal of Neuroradiology, 2025)
The inner ear contains many fissures and canals that can mimic pathology. Photon-counting CT allows greater spatial and contrast resolution of these structures over traditional energy-integrating CT detectors. Small channels containing nerves, arteries, and normal anatomy such as the cochlear cleft and cochlear and vestibular aqueducts are commonly encountered on temporal bone imaging. The improved visualization of these structures poses challenges for radiologists who are new to photon-counting CT. This article updates the existing temporal bone anatomy literature with a detailed anatomic review of the inner ear and major nerves frequently encountered when reviewing temporal bone imaging.EIDenergy-integrating detectorFAFfissula ante fenestramIACinternal auditory canalPCTphoton-counting CT